Una fiesta con pizza! - Maccarone, Grace; McCully, Emily Arnold (New York : Scholastic, 2003)
A group of children have fun making a pizza.
"Cartwheel books."
Keywords: Pizza -- Juvenile fiction; Stories in rhyme; Spanish language materials -- Juvenile fiction